Indigenous Community Governance: Challenging State-Centric Approaches to Food Security with Evidence from Kasepuhan Ciptagelar, Indonesia - Ujang Wahid Muhammad Abdillah (Journal of International Conference Proceedings, 2025)
This study examines indigenous food governance in the Kasepuhan Ciptagelar community of West Java, Indonesia, as an alternative to state-centric approaches to food security. Employing a qualitative hermeneutic method within the Social-Ecological Systems (SES) framework, the study analyzes secondary data from documentary films, academic literature, and media reports through thematic coding focused on governance systems. The findings reveal that Ciptagelar has sustained food self-sufficiency for centuries despite national dependence on imports, where Indonesia imported 4.52 million tons of rice in 2024. Empirically, the community manages approximately 12,000 leuit (traditional granaries), with rice reserves estimated to be sufficient for up to 95 years. Rice is treated as a sacred resource, prohibited from commodification, and regulated through annual agricultural cycles reinforced by rituals such as Seren Taun and Ponggokan. These findings challenge the assumption that effective food governance must operate under state hierarchy and extend the SES framework by emphasizing cultural and spiritual legitimacy. The study suggests that indigenous governance systems can inform more inclusive and resilient food security policies.